Lessons from implementation models in Bangladesh - Mitra, Archisman (International Water Management Institute, 2024)
Diesel dependency creates energy insecurity and puts a financial burden on the country. To improve energy security, protect farmers from fuel price shocks and also reduce emissions from diesel usage, Bangladesh Government is promoting the implementation and use of solar irrigation pumps (SIPs). The study encountered three solar irrigation models as: (a) Free-for- Service (b) Individual Ownership model and (c) Community managed models in the country. Among these, the Free-for-Service model exhibited multiple benefits as this is funded by Infrastructure Development Company Limited (IDCOL) a private company and is widely used among farmers of Bangladesh and it accounts for the ease of investment and financial viability of the system installed. Ultimately no single model fits all locations and they have to be context-specific and determined by the objectives.